MUE563 : Digital technology in music education / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
This course introduces the students to methods of compiling and creating teaching and learning materials using digital technology namely multi track recording, digital score writing, and digital desktop publishing. Students will be equipped with basic skills of how to design and develop a complete teaching kit for classroom use utilizing related software available. Students are also introduced to various computer aided instructions program available as standalone and online, and creation of test/exam papers.